Local Explicit Many-Knot Spline Hermite Approximation Schemes (Journal of Computational Mathematics, 2021)
If $f^{(i))}(α)(α=a, i=0,1,...,k-2)$ are given, then we get a class of the Hermite approximation operator Qf=F satisfying $F^{(i)}(α)=f^{(i)}(α)$, where F is the many-knot spline function whose knots are at points $y_i:$=$y_0$